Swot Analysis, Social Media And Promotional Video As Marketing Strategy In Mie Pangsit Ayam Bangka Mr. Dodo - Evi Silvana Muchsinati; Marcerllina Teo (Universitas Internasional Batam, 2021)
Mie Pangsit Ayam Bangka Mr. Dodo is a small medium enterprise business. It was founded by Mr. Liu Kuan Lie or to be called as Pak Ado at Ruko Grand Orchid Block A3 No. 10. Average income from the business itself per year is Rp 142,000,000 with an estimated average buyer of 22 people per day. The problems that they are facing right now are the lack of promotion which leads to making it difficult to bring in new customers, has never done a digital promotions such as do not have a social media account, and the location of the place which tends to be quiet. Methods in data collection used are by conducting interviews, observation, and from secondary data. The results obtained after a SWOT analysis were carried out, the authors got the results to be able to implement marketing strategy by creating an Instagram social media account and by making promotional video. Recommendations given to the business owner is to used the social media that has been created consistently.